Performance of crossbred cattle (HF × Sahiwal) under tropical farming conditions of Punjab - KUMAR, RAVINDER; DAS, A K; RAJA, T V; RATHEE, S K; DUBEY, P P; PRAKASH, B (The Indian Journal of Animal Sciences, 2017)
The present study was focused to estimate the effect of certain genetic and non-genetic factors, viz. sire, season and period on the AFC, MY, PY and fat % of crossbred cattle of farmers reared under the tropical conditions of Punjab state of India. The records on first lactation milk yield and reproduction performance of 3,008 crossbred cattle spread over a period of 18 years (1995-2012) were used for the study to assess the impact of crossbred cattle performance in this area. The production traits considered were age at first calving (AFC), first lactation 305-days or less milk yield (FL305DMY), peak yield (PY) and fat%. The overall least squares means for AFC, MY, PY and fat% were estimated as 1092.009±07.96 (days), 3214.488±26.58 kg, 12.922±0.10 kg and 3.739±0.01%, respectively. The effect of sire was highly significant on all the traits while the effect of season was significant on MY, peak yield and fat%. However, the effect of period was highly significant on MY and fat% only. It is also reflected that the fluctuations in extreme climatic conditions did affect these traits in milch crossbred cattle maintained under tropical farming conditions. The heritability estimates of different production traits, viz. FL305DMY, PY and fat% were 0.316±0.054, 0.177±0.042 and 0.064±0.032, respectively.